Antibacterial Activity Testing of Red Dragon Fruit Peel On Pseudomonas Sp. - Diah Setiani (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research was conducted using a completely randomized design (CRD) one factor, namely red dragon fruit peel with concentrations of 15%, 25%, 50%, 75%, and 95%, respectively. The positive control is amoxicillin and the negative control is sterile aquadest. The study began on August 12, 2019, until November 14, 2019, at the Laboratory of the TLM Health Polytechnic of Ministry of Health East Kalimantan. The data obtained were analyzed descriptively. The results showed the inhibitory concentration of Staphylococcus Aureus bacteria with the highest inhibition zone diameter was on the decoction of red dragon fruit peel with a concentration of 95%, which is 16 mm (moderate inhibitory power). While the minimum inhibitory concentration is produced by a decoction of red dragon fruit peel with a concentration of 25% with a diameter of 9 mm.